Biomimetic synthesis of (−)-chaetominine epimers via copper-catalyzed radical cyclization. Issue 22 (3rd June 2015) - Deng, Xu; Liang, Kangjiang; Tong, Xiaogang; Ding, Ming; Li, Dashan; Xia, Chengfeng
Abstract: Synthetic endeavors toward (−)-chaetominine via copper-catalyzed radical cyclization are reported. Both of the pyrido[2, 3, b ]-indole ring (C ring) and imidazolidinone (D ring) are efficiently constructed in one-pot manner. It's unveiled that the newly formed stereo center is controlled by the chiral of alanine, not by tryptophan. With these synthetic discoveries, highly efficient and diastereoselective synthesis of (+)-2, 3, 14- epi -chaetominine5 and (−)-11- epi -chaetominine11 is achieved. Graphical abstract: